Pengaruh Model Problem Based Learning Berbantuan Media PhET Simulation terhadap Pemahaman Konsep IPA Siswa SD - Mutiah Mutiah; Khairunnisa Nisa; Santi Febriani; Nazwa Aulia Zahra; Nasha Indri Fazila; Benardo Manalu; Afridha Laily Alindra (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
Primary school students' understanding of science concepts remains low due to teacher-centered learning and minimal use of supporting media. This condition indicates the need for a learning model that can increase active participation and facilitate meaningful inquiry activities. This study aims to determine the effect of the PhET Simulation-assisted Problem Based Learning model on the ability to understand science concepts in energy change material. This study used a quantitative method with a One Group Pretest Posttest Design involving 22 fourth-grade students at an elementary school in Purwakarta. The research instrument was a multiple-choice test based on seven concept comprehension indicators. The data were analyzed using descriptive statistics, Shapiro Wilk normality test, Wilcoxon test, and N Gain calculation. The results showed an increase in conceptual understanding after the learning model was implemented, as indicated by an increase in the average pretest score to the average posttest score and an N Gain score of 0.73 in the high category. The Wilcoxon test confirmed a significant difference between the initial ability and the ability after the treatment. These findings confirm that PhET Simulation-assisted Problem Based Learning is effective in supporting science concept comprehension and has the potential to be a more interactive and meaningful learning alternative for elementary school students.